Macromol. Rapid Commun. 3/2015. Issue 3 (February 2015) - Guo, Song; Fan, Hong; Bu, Zhiyang; Li, Bo‐Geng; Zhu, Shiping
<x xml:space="preserve">Abstract</x> Back Cover: A synthetic method for the preparation of ultrahigh‐molecular‐weight ethylene/high α‐olefin copolymers via living coordination polymerization is provided. In a fluorinated FI‐Ti catalyst system, the molecular weight and 1‐hexene incorporation of the resultant ethylene/1‐hexene copolymers can exceed 1.4 × 106 g/mol and 25 mol%, respectively, and the PDI remains smaller than 1.4. The product of the reactivity ratios r1r2 is close to 1, giving random unit distributions. Further details can be found in the article by S. Guo, H. Fan, Z. Bu, B.‐G. Li, * and S. Zhu* on page 286. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>